2019
DOI: 10.1002/cnma.201800667
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Oxidation Stability of Transparent Copper Films Using a Hybrid Organic‐Inorganic Nucleation Layer

Abstract: A novel seed layer for the formation of slab‐like transparent copper films on glass and plastic substrates is reported, based on a mixed molecular monolayer and an ultra‐thin (0.8 nm) aluminium layer both deposited from the vapour phase, which substantially outperforms the best nucleation layer for optically thin copper films reported to date. Using this hybrid layer, the metal percolation threshold is reduced to <4 nm nominal thickness and the long‐term stability of sub‐10 nm films towards oxidation in air is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Previous work by our group and has shown that the morphology, resistivity and stability of optically thin Ag and Cu films toward oxidation in air is strongly dependent on the strength of interaction with the underlying substrate. [22,45] This is because metal films that bind strongly to the underlying substrate form compact slab-like morphologies at low film thickness that are inherently more resistant to oxidation and morphological change. [22,45,46] In the current case the resistance of the Cu electrode actually decreases upon constant illumination for 20 h in ambient air, which evidences the fact that Cu films oxidize extremely slowly in air; ii) and/or the much lower cohesion energy of Ag atoms as compared to Cu; −249 kJ mol −1 versus −422 kJ mol −1 , respectively, in the bulk.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work by our group and has shown that the morphology, resistivity and stability of optically thin Ag and Cu films toward oxidation in air is strongly dependent on the strength of interaction with the underlying substrate. [22,45] This is because metal films that bind strongly to the underlying substrate form compact slab-like morphologies at low film thickness that are inherently more resistant to oxidation and morphological change. [22,45,46] In the current case the resistance of the Cu electrode actually decreases upon constant illumination for 20 h in ambient air, which evidences the fact that Cu films oxidize extremely slowly in air; ii) and/or the much lower cohesion energy of Ag atoms as compared to Cu; −249 kJ mol −1 versus −422 kJ mol −1 , respectively, in the bulk.…”
Section: Resultsmentioning
confidence: 99%
“…[22,45] This is because metal films that bind strongly to the underlying substrate form compact slab-like morphologies at low film thickness that are inherently more resistant to oxidation and morphological change. [22,45,46] In the current case the resistance of the Cu electrode actually decreases upon constant illumination for 20 h in ambient air, which evidences the fact that Cu films oxidize extremely slowly in air; ii) and/or the much lower cohesion energy of Ag atoms as compared to Cu; −249 kJ mol −1 versus −422 kJ mol −1 , respectively, in the bulk. [47] A lower cohesion energy means that metal atoms at the surface of the metal crystallites can move more easily, enabling more facile morphological change at low temperature; iii) and/or a difference in the rate of surface oxide formation, which is important because morphological change requires diffusion of metal atoms over the crystallite surfaces-a process that is impeded by the formation of an oxide layer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this approach, in conjunction with a high-refractive index anti-reflection layer, a sheet resistance of ∼9 /sq and a remarkable transmittance of ∼93% is demonstrated together with outstanding long-term environmental and mechanical stability. Whilst to date studies reporting hybrid organic-inorganic metal nucleation layers are sparse (Bellchambers et al, 2019). Wang et al have shown that the benefits can be substantial and in some cases may off-set the disadvantage associated with the extra complexity in fabrication.…”
Section: Editorial On the Research Topic Window Electrodes For Emergimentioning
confidence: 99%
“…These seeds provide dense nucleation centers for metal deposition, and suppress the growth of large metal islands during the PVD process. Such functional seeding materials include metals (Al, [40][41][42] Au, [43] Ag, [44] and Cu [45] ), dielectrics (Ta 2 O 5 , [46] ZnO, [47][48][49] NiO, [50] TeO 2 , [51] Nb 2 O 5 , [52] MoO 3 , [53] and Cs 2 CO 3 [54] ), polymers (polyethyleneimine [PEI], [19,[55][56][57][58] Ormoclear, [59] and photoresist SU-8 [60] ), and organic monolayers (11-mercaptoundecanoic acid [MUA], [48] [3-aminopropyl]-trimethoxysilane: [3mercaptopropyl]-trimethoxysilane [APTMS:MPTMS], [42,61,62] methyl-terminated alucone, [63] and 1,4-bis[2-phenyl-1,10-phenanthrolin-4-yl]benzene [p-bPPhenB] [64] ). For example, Schubert et al enhanced the wetting of deposited Ag films by using high surface energy metal seed materials such as Ca, Al, and Au (Figure 2a).…”
Section: Introductionmentioning
confidence: 99%